2018
DOI: 10.1039/c8cp00691a
|View full text |Cite
|
Sign up to set email alerts
|

Is a cross-β-sheet structure of low molecular weight peptides necessary for the formation of fibrils and peptide hydrogels?

Abstract: Short peptides have emerged as versatile building blocks for supramolecular structures and hydrogels. In particular, the presence of aromatic amino acid residues and/or aromatic end groups is generally considered to be a prerequisite for initiating aggregation of short peptides into nanotubes or cross β-sheet type fibrils. However, the cationic GAG tripeptide surprisingly violates these rules. Specifically, in water/ethanol mixtures, GAG peptides aggregate into very long crystalline fibrils at temperatures bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 59 publications
4
33
0
Order By: Relevance
“…This is consistent with expected distances between strands of a β‐sheet or between β‐sheets in stacks, respectively 32 . This does not necessarily mean that the fibrils form β‐sheets, similar distances can be expected for alternative arrangements 31 …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with expected distances between strands of a β‐sheet or between β‐sheets in stacks, respectively 32 . This does not necessarily mean that the fibrils form β‐sheets, similar distances can be expected for alternative arrangements 31 …”
Section: Resultssupporting
confidence: 86%
“…The powder and fibril spectra show a sharp split of the amide I profile into bands at 1644 cm −1 (AI 1 ) and 1673 cm −1 (AI 2 ). For the peptide powder, the peak intensity for AI 1 is twice that of the AI 2 peak intensity, which indicates substantial excitonic coupling between individual amide I modes and thus a rather high degree of molecular order 31 . The fibrils' spectrum shows a qualitatively similar doublet but a reduced peak intensity ratio (i.e., AI 1 /AI 2 = 1.2 for phase I and slightly below 1 for phase II).…”
Section: Resultsmentioning
confidence: 94%
“…It would also be possible to calculate the effect of biosurfactant addition on the interfacial tension in a two-phase system and to estimate lateral and rotational diffusion of the peptide ring [68]. Studies on the use of biomolecules such as surfactin can also be supplemented with modeling of molecular structure using density functional theory (DFT), which includes dispersion interactions and peptide bonds in peptide-based systems [69].…”
Section: Resultsmentioning
confidence: 99%
“…17 For the present study we used the optimized geometry of these two conformations in TDDFT calculations at the ωB97X-D/cc-pVTZ level of theory to calculate the UVCD and corresponding absorption spectra of GAG in implicit and explicit water. 17 We specifically chose the ωB97X-D functional for our studies since it contains an asymptoticallycorrect (range-separated) portion of nonlocal exchange in conjunction with dispersion corrections, which are essential for accurately predicting charge-transfer excitations and hydrogenbonding interactions, 18 respectively. It is also important to note that prior work by Neto et al 19 has shown that the optimal range-separated parameter, ω, required to accurately predict excited-states in explicit solvent is 0.25, which is already close to the default value of ω = 0.2 used in the ωB97X-D functional.…”
mentioning
confidence: 99%